Characterization of Cracks and their Effects on the Effective Transport Pathways in Ni-YSZ Anodes after Reoxidation Using X-Ray Nanotomography. (2nd June 2015) - Nakajo, Arata; Kiss, Andrew M.; Cocco, Alex P.; Harris, William M.; DeGostin, M. B.; Greco, Fabio; Nelson, George J.; Peracchio, Aldo A.; Cassenti, Brice N.; Deriy, Alex; Wang, Steve; Chen-Wiegart, Yuchen; et al.
Abstract : Reduction-oxidation cycling of Ni-based electrodes for solid oxide fuel/electrolysis cells irreversibly alters their microstructure and can cause the fracture of the electrolyte. Non-destructive 3-D imaging enables tracking of microstructural changes that occur during cycling. Despite recent advances, the understanding of how local 3-D geometrical features in the heterogeneous electrode material contribute to the material degradation remains incomplete. Absorption contrast X-ray nanotomography (XNT) of a same Ni(O)-yttria-stabilized zirconia (YSZ) sample was performed at the Ni K-edge white-line peak (8348 eV), before and after exposure to air at 800°C during 45 minutes. A complimentary XNT at 8376 eV confirmed a degree of oxidation higher than 98%. The morphology of the Ni(O) phase was as expected completely different after re-oxidation. The spatial resolution better than 20 nm enabled the detection of cracks in the brittle YSZ phase above this dimension. The detrimental effects of the cracks on the effective 3-D transport pathways in the Ni-YSZ anode under polarization was investigated using a skeleton-based discrete representation of the imaged volume and an analytical electrochemical fin model. Topological properties, effective ionic conductivity and polarization resistance were calculated before and after oxidation. For the latter estimate, the effect of the cracked YSZ network was considered alone so far; that of the spatial re-distribution of triple-phase boundaries induced by re-oxidation will be included in the future. Cracks in the brittle YSZ phase induced an increase in the effective ionic resistivity and in the polarization resistance in the range of 25 ± 9% and 12 ± 5%, respectively.